Pushed by Pain or Pulled by Vision: Transformational Leadership and Its Implications on Curriculum Reform within Higher Education Institutions in the Khmer Context - Sarom Mok; Neavea Tep; Satya Yen; Mengheang Hor; Pisith Hok; Chamnab Voeun (PT Mattawang Mediatama Solution, 2026)
Higher education institutions (HEIs) are under growing pressure to change their curricula in order to promote sustainability, creativity, and equity in an educational environment that is changing quickly due to new trends and labor demands. The issue is that the Khmer HEI faculty members continue to struggle to undertake meaningful curricular change. Studies on the impact of transformational leadership on curriculum reform in HEIs are scarce in the literature, despite the expanding corpus of research on curriculum implementation. This fundamental qualitative study aims to investigate the effects of transformational leadership on curricular reform among faculty members in the Khmer HEIs. The theoretical frameworks employed in this study were: (i) change leadership theory; and (ii) reconceptualist curriculum theory. The purpose of this study was to investigate how transformational leadership behaviors and methods affect curriculum reform in the Khmer HEIs. Twenty-five people were chosen to make up the sample from the target demographic of the Khmer HEI faculty members using purposeful sampling. Each participant had to meet three requirements for inclusion: they had to be employed at the research location for at least three years, be knowledgeable about curriculum reform, and have a theoretical grasp of transformational leadership. Semi-structured interview techniques were used to gather the data, and the NVivo was used to analyze it using Braun and Clarke’s (2019) theme analysis methodology. This study illustrated the beneficial effects of transformational leadership behaviors and techniques on curriculum reform in the Khmer HEIs. The results demonstrated that through enhancing engagement and communication, boosting support, promoting diversity, and facilitating knowledge sharing and collaboration, transformational leadership behaviors and techniques helped the Khmer HEIs alter their curricula. The findings of this study may help policymakers and educational leaders implement successful leadership models to assist curriculum reform by leading to better academic results and institutional change in higher education.